+0  
 
0
76
1
avatar

show your work solve for x - 4x+3=5x-2

Guest Oct 4, 2017

Best Answer 

 #1
avatar+5573 
+1

x - 4x + 3  =  5x - 2       Subtract  3  from both sides of the equation.

 

x  -  4x  =  5x - 2 - 3      Subtract  5x  from both sides of the equation.

 

x - 4x - 5x  =  -2 - 3       Combine like terms.

 

-8x  =  -5               Divide both sides by  -8 .

 

x  =  -5 / -8

 

x  =  5 / 8

hectictar  Oct 4, 2017
Sort: 

1+0 Answers

 #1
avatar+5573 
+1
Best Answer

x - 4x + 3  =  5x - 2       Subtract  3  from both sides of the equation.

 

x  -  4x  =  5x - 2 - 3      Subtract  5x  from both sides of the equation.

 

x - 4x - 5x  =  -2 - 3       Combine like terms.

 

-8x  =  -5               Divide both sides by  -8 .

 

x  =  -5 / -8

 

x  =  5 / 8

hectictar  Oct 4, 2017

4 Online Users

We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details